Effect of Triangular Lip Wall on the Performance of a Stationary Oscillating Water Column Device at Various Wave Conditions Using Reynolds-averaged Navier-Stokes (RANS) Model - R. Ranjan Manjul; P. Deb Roy (Journal of Applied Fluid Mechanics)
One of the most inexhaustible forms of energy is the ocean wave. The conversion of this energy into a useful form of electrical energy is possible by a device of oscillating water column (OWC). This work aims to numerically analyse the effect of the triangular lip wall of the OWC wave energy converter on the hydrodynamic efficiency at different wave steepness conditions (Hi/λ), orifice ratios (ε), and relative openings (σ). This analysis uses commercial computational fluid dynamics (CFD) code ANSYS FLUENT software in a 3D numerical wave tank. The governing equations are discretized using FVM formulation, and the k-ε turbulence model is used. The inlet velocity method is used to generate the waves. The model was validated and verified with the experimental model published by Çelik and Altunkaynak (2019) and implemented for further improvement. The hydrodynamic efficiency (Eff) of the new model increases with relative openings increases and also increases with the decreases in wave steepness. This study shows an optimum efficiency of 76.30% at ε4 = 1.03%, σ =75%, and Hi/λ = 0.02. The information obtained from this numerical investigation of a new model is a highly relevant source, and it provides foresight in the design of the OWC wave energy converter.